Regulation of genetically engineered (GE) mosquitoes as a public health tool: a public health ethics analysis - Zahra Meghani (BMC, 2022)
Abstract Background In recent years, genetically engineered (GE) mosquitoes have been proposed as a public health measure against the high incidence of mosquito-borne diseases among the poor in regions of the global South. While uncertainties as well as risks for humans and ecosystems are entailed by the open-release of GE mosquitoes, a powerful global health governance non-state organization is funding the development of and advocating the use of those bio-technologies as public health tools. In August 2016, the US Food and Drug Agency (FDA) approved the uncaged field trial of a GE Aedes aegypti mosquito in Key Haven, Florida. The FDA's decision was based on its assessment of the risks of the proposed experimental public health research project. The FDA is considered a global regulatory standard setter. So, its approval of the uncaged field trial could be used by proponents of GE mosquitoes to urge countries in the global South to permit the use of those bio-technologies. Method From a public health ethics perspective, this paper evaluates the FDA's 2016 risk assessment of the proposed uncaged field trial of the GE mosquito to determine whether it qualified as a realistic risk evaluation. Results The FDA's risk assessment of the proposed uncaged field trial did not proximate the conditions under which the GE mosquitoes would be used in regions of the global South where there is a high prevalence of mosquito-borne diseases. Conclusion Given that health and disease have political-economic determinants, whether a risk assessment of a product is realistic or not particularly matters with respect to interventions meant for public health problems that disproportionately impact socio-economically marginalized populations. If ineffective public health interventions are adopted based on risk evaluations that do not closely mirror the conditions under which those products would actually be used, there could be public health and ethical costs for those populations.